Oil well cementing cement slurry system and application thereof

By using high-temperature stabilizers such as quartz sand, microsilicon powder and nanosilicon dioxide in the cementing cement slurry of oil wells, combined with high-temperature enhancers such as leaf wax stone, cement stone with high compressive strength and durability, the current solution is solved There is a problem of cement slurry's strength decline at high temperatures, which is suitable for cementing deep ultra-deep oil and gas wells.

CN119176694AActive Publication Date: 2024-12-24CHINA PETROLEUM & CHEMICAL CORP +1

Patent Information

Application Number
CN202310743561.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24
Estimated Expiration
2043-06-21

AI Technical Summary

Technical Problem

The strength of the existing cement slurry system declines at temperatures above 150°C, which cannot effectively solve the problem of strength reduction in cementing of high-temperature deep wells.

Method used

The cementing slurry system of oil wells containing quartz sand, microsilicon powder and nanosilicon dioxide, as well as high-temperature enhancers such as sachetite, chlorite, and yanglithite, is adopted to pass particle grading and hydration reaction. Control to form cement stone with high compressive strength and durability.

Benefits of technology

In a high temperature environment of 150-240℃, the compressive strength of the cement slurry system does not decline and continues to grow, maintaining good durability and suspension stability, meeting the technical requirements for cementing construction of deep ultra-deep oil and gas wells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of oil and gas well cementation, and discloses an oil well cementation cement slurry system and application thereof. The cement paste system comprises the following components in parts by weight: 100 parts of oil well cement, 20-80 parts of a high-temperature stabilizer, 15-80 parts of a high-temperature reinforcing agent, 0.5-6 parts of a retarder, 2-10 parts of a fluid loss agent, 0.1-2 parts of a defoaming agent and 35-90 parts of water, wherein the high-temperature stabilizer is a mixture containing quartz sand, silica fume and nano-silica which are different in average particle size; the high-temperature reinforcing agent is selected from at least one of pyrophyllite, epidote, actinolite, aluminum stone, sillimanite and boehmite. The cement paste system is mixed by adopting a conventional method, the density and the thickening time are adjustable, the flowing property is good, the water loss is small, the strength of formed cement stone is high, the cement stone does not decline for a long time at the high temperature of 150-240 DEG C, and the technical requirements of deep and ultra-deep high-temperature and high-pressure well cementation construction are completely met.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of oil and gas well cementing, and in particular to an oil well cementing slurry system and application thereof. Background Art

[0002] my country has rich deep and ultra-deep oil and gas resources and great potential. According to statistics, China's deep and ultra-deep oil and gas resources amount to 671×10 8 t oil equivalent, accounting for 34% of the total oil and gas resources, 39% of the remaining oil and 57% of the remaining natural gas resources are distributed in deep and ultra-deep layers. Accelerating the exploration and development of deep and ultra-deep oil and gas is the focus and hotspot of current and future oil and gas exploration and development.

[0003] Cementing is an important part of the oil and gas well construction process, and is the premise and foundation for the safe and efficient development of oil and gas resources. Cementing is to pump cement slurry through the drill pipe or casing into the annular space between the wellbore and the casing through cement pump trucks and other equipment on the ground, and solidify to form a hard cement ring, ultimately achieving the purpose of protecting and hanging the casing and isolating the formation, so as to facilitate subsequent safe drilling and production. In the exploration and development of deep and ultra-deep oil and gas, we often face complex environments such as high temperature and high pressure. The high-temperature strength decline of silicate oil well cement used for conventional oil and gas well cementing is one of the key factors affecting the quality of high-temperature deep well cementing. Studies have shown that 110℃ and 150℃ are the critical points for the high-temperature strength decline of cement stone. Adding 30%-40% quartz sand in the temperature range of 110-150℃ can meet the high-temperature strength stability, but after exceeding 150℃, it only partially alleviates the strength decline, but cannot solve the strength decline problem.

[0004] Therefore, there is an urgent need for a cement slurry system, which can form a cement paste whose strength does not decline under temperature conditions above 150°C. Summary of the invention

[0005] The purpose of the present invention is to overcome the problem that after the cement slurry system in the prior art forms cement stone, when the curing temperature exceeds 150°C, the sand-added oil well cement causes the transformation of hydration products, resulting in reduced strength and increased permeability of the cement stone, and to provide an oil well cementing cement slurry system and its application, wherein the cement slurry system has excellent resistance to high temperature strength decay.

[0006] In order to achieve the above object, the first aspect of the present invention provides an oil well cementing cement slurry system, wherein the cement slurry system comprises the following components in parts by weight: 100 parts of oil well cement, 20-80 parts of high temperature stabilizer, 15-80 parts of high temperature enhancer, 0.5-6 parts of retarder, 2-10 parts of fluid loss reducer, 0.1-2 parts of defoamer and 35-90 parts of water;

[0007] Wherein, the high temperature stabilizer is a mixture of quartz sand, microsilica powder and nano silicon dioxide having different average particle sizes;

[0008] The high temperature enhancer is selected from at least one of pyrophyllite, epidote, actinolite, diaspore, sillimanite and boehmite.

[0009] A second aspect of the present invention provides an application of the cement slurry system provided by the present invention in high-temperature deep well cementing.

[0010] Through the above technical solution, the beneficial effects of the present invention are:

[0011] The cement slurry system of the present invention can adapt to the formation temperature environment of 150-240°C, and the conventional density (1.88-1.9g / cm 3 ) The compressive strength of the cement stone formed after the cement slurry system solidifies is above 35MPa after curing for 60 days, with no strength decay and continuous growth, and has good durability. The cement slurry system of the present invention has good water retention and thickening properties, and can maintain the suspension stability of the cement slurry under high temperature conditions without adding a suspension stabilizer. The cementing cement slurry system of the present invention is mixed by conventional methods, and the density and thickening time are adjustable, the flowability is good, the water loss is small, the compressive strength and flexural strength are high, and it does not decay at high temperatures, and fully meets the technical requirements of on-site cementing construction.

[0012] In a preferred embodiment of the present invention, by selecting quartz sand, microsilica powder and nano-silica of suitable size and proportion to be blended as a high-temperature stabilizer, on the one hand, a close packing effect is achieved through particle grading, thereby improving the strength of cement paste and reducing the porosity and permeability of cement paste; on the other hand, the rate and process of silica participating in the hydration reaction are controlled by using crystalline quartz sand, amorphous microsilica powder and nano-silica of different particle sizes; the present invention selects a high-temperature enhancer with a reasonable matching method, raw material ratio and size, and by adding a high-temperature enhancer, the cement hydration product can be better inhibited from transforming into a high calcium-silicon ratio product, so that the cement paste maintains a dense structure; the present application selects a toughening agent of suitable type and size, and by adding a toughening agent, on the one hand, it can become a hydration nucleation point to induce hydration, and on the other hand, it can serve as a structural support point to improve the strength and toughness of cement paste. The high-temperature stabilizer, high-temperature enhancer and toughening agent selected by the present invention have a good synergistic effect, further improving the compressive strength of the cement paste formed by the cement slurry system. DETAILED DESCRIPTION

[0013] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0014] The first aspect of the present invention provides an oil well cementing slurry system, the slurry system comprising the following components in parts by weight: 100 parts of oil well cement, 20-80 parts of high temperature stabilizer, 15-80 parts of high temperature enhancer, 0.5-6 parts of retarder, 2-10 parts of fluid loss reducer, 0.1-2 parts of defoamer and 35-90 parts of water;

[0015] Wherein, the high temperature stabilizer is a mixture of quartz sand, microsilica powder and nano silicon dioxide having different average particle sizes;

[0016] The high temperature enhancer is selected from at least one of pyrophyllite, epidote, actinolite, diaspore, sillimanite and boehmite.

[0017] The use of quartz sand, microsilica powder and nano-silica in high-temperature stabilizers, on the one hand, achieves a close packing effect through particle grading, improves the strength of cement paste, and reduces the porosity and permeability of cement paste; on the other hand, by using crystalline quartz sand, amorphous microsilica powder and nano-silica of different particle sizes, the rate and process of silica participating in the hydration reaction are controlled, thereby improving the strength of cement. Quartz sand, microsilica powder and nano-silica cooperate with each other to improve the strength of cement paste. Pyrophyllite has hydroxyl-containing aluminum silicate minerals, epidote has hydroxyl-containing iron aluminum calcium silicate minerals, actinolite has hydroxyl-containing iron magnesium calcium silicate minerals, sillimanite has glassy aluminum silicate minerals with columnar or needle-shaped structures, and diatomite and boehmite are aluminum-rich bauxite. Using these minerals as high-temperature enhancers can inhibit the transformation of cement hydration products to high calcium-silicon ratio products, so that the cement paste maintains a dense structure. The high temperature stabilizer and the high temperature enhancer cooperate with each other to improve the strength of cement. The high temperature stabilizer and the high temperature enhancer cooperate with the retarder, the fluid loss reducer and the defoamer to obtain a cement slurry system with excellent resistance to high temperature strength decline.

[0018] According to a preferred embodiment of the present invention, the cement slurry system comprises the following components in parts by weight: 100 parts of oil well cement, 40-50 parts of high temperature stabilizer, 30-40 parts of high temperature enhancer, 2.5-4.5 parts of retarder, 7-8 parts of fluid loss reducer, 0.4-0.6 parts of defoamer and 50-60 parts of water.

[0019] According to the present invention, preferably, the oil well cement is Grade G cement.

[0020] According to the present invention, preferably, the average particle size of the quartz sand is 75-180 μm, the average particle size of the microsilica is less than or equal to 10 μm, and the average particle size of the nano-silica is 1-100 nm. When the average particle sizes of the quartz sand, microsilica and nano-silica meet this range, a good close packing effect can be achieved through particle grading, the strength of the cement paste is improved, and the porosity and permeability of the cement paste are reduced.

[0021] Furthermore, the average particle size of the quartz sand is 80-110 μm, the average particle size of the microsilica powder is 8-10 μm, and the average particle size of the nano-silicon dioxide is 20-30 nm.

[0022] According to the present invention, preferably, the weight ratio of the quartz sand, the microsilica powder and the nano-silica contained in the high temperature stabilizer is (10-25): (3-5): 1. When quartz sand, microsilica powder and nano-silica are mixed in this weight ratio as a high temperature stabilizer, the stacking rate can be increased, a dense stacking effect can be achieved, and the structure of the cement stone can be improved.

[0023] According to the present invention, preferably, the average particle size of the high temperature enhancer is 5-80 μm. When the average particle size of the high temperature enhancer meets this range, the stacking rate can be improved, the close stacking effect can be enhanced, and appropriate activity can be maintained to promote the transformation of hydration products.

[0024] According to the present invention, preferably, the high temperature enhancer is a mixture of epidote and boehmite, a mixture of pyrophyllite and sillimanite, or a mixture of pyrophyllite and actinolite. Using a mixture of epidote and boehmite as a high temperature enhancer, a mixture of pyrophyllite and sillimanite, a mixture of pyrophyllite and actinolite, or a mixture of pyrophyllite and actinolite as a high temperature enhancer can synergistically enhance the inhibition of cement hydration products to high calcium-silicon ratio products, and further inhibit the coarsening of the crystal structure of the hydration products.

[0025] According to the present invention, preferably, the high temperature enhancer is a mixture of epidote with an average particle size of 40-50 μm and boehmite with an average particle size of 10-15 μm, a mixture of pyrophyllite with an average particle size of 40-50 μm and sillimanite with an average particle size of 20-30 μm, or a mixture of pyrophyllite with an average particle size of 40-50 μm and actinolite with an average particle size of 70-80 μm.

[0026] According to the present invention, preferably, when the high temperature enhancer is a mixture of epidote and boehmite, epidote and boehmite are mixed in a weight ratio of (20-30): (3-10); when the high temperature enhancer is a mixture of pyrophyllite and sillimanite, pyrophyllite and sillimanite are mixed in a weight ratio of (20-30): (5-15); when the high temperature enhancer is a mixture of pyrophyllite and actinolite, pyrophyllite and actinolite are mixed in a weight ratio of (20-30): (5-20). When the high temperature enhancer is a mixture mixed in the above ratios, it can synergistically enhance the inhibition of cement hydration products to high calcium-silicon ratio products, and further inhibit the coarsening of the crystal structure of the hydration products.

[0027] According to the present invention, preferably, the retarder is selected from at least one of inorganic acid, 2-acrylamide-2-methylpropanesulfonic acid (AMPS) copolymer, tartaric acid, citric acid and phosphate, preferably a mixture of tartaric acid and AMPS copolymer. Among them, the AMPS copolymer can be a copolymer of 2-acrylamide-2-methylpropanesulfonic acid (AMPS), N-vinyl pyrrolidone (NVP) and itaconic acid (LA). The present invention has no special restrictions on the weight average molecular weight of the AMPS copolymer and the proportion of the structural units contained in the AMPS copolymer, as long as the performance as a retarder can be met. For example, an AMPS copolymer purchased from the Texas Continental Shelf with a brand name of SCR180L can be selected. Using a mixture of tartaric acid and AMPS copolymer as a retarder can synergistically enhance the inhibitory effect on cement hydration and improve the retarding effect under high temperature conditions.

[0028] According to the present invention, preferably, the weight ratio of tartaric acid to AMPS multipolymer is (1-5):(5-20). Mixing tartaric acid and AMPS multipolymer in this weight ratio as a retarder can synergistically enhance the inhibition of cement hydration and improve the retarding effect under high temperature conditions.

[0029] According to the present invention, preferably, the fluid loss additive is a polymer.

[0030] According to the present invention, preferably, the polymer is a copolymer comprising a structural unit derived from 2-acrylamido-2-methylpropanesulfonic acid (AMPS) and a structural unit derived from acrylamide.

[0031] The present invention has no particular restrictions on the weight average molecular weight of the polymer and the weight ratio of the structural units derived from 2-acrylamido-2-methylpropanesulfonic acid and the structural units derived from acrylamide contained in the polymer, as long as the performance as a fluid loss reducer is satisfied. For example, a copolymer of AMPS and acrylamide purchased from Texas Continental Shelf with a brand name of SCF-J can be selected.

[0032] According to the present invention, preferably, the defoamer is selected from silicone defoamers and / or tributyl phosphate defoamers. When the defoamer is a mixture of silicone defoamers and tributyl phosphate defoamers, the silicone defoamers and tributyl phosphate defoamers can be mixed in any proportion.

[0033] Furthermore, the defoaming agent is a silicone defoaming agent.

[0034] According to the present invention, preferably, the cement slurry system further comprises less than 5 parts by weight of a toughening agent. The high-temperature stabilizer can control the rate and process of silica participating in the hydration reaction, thereby improving the strength of cement; the high-temperature enhancer can inhibit the transformation of cement hydration products to high calcium-silicon ratio products, so that the cement stone maintains a dense structure; the toughening agent can become a hydration nucleation point to induce hydration, and on the other hand, it can serve as a structural support point to improve the strength and toughness of the cement stone. When less than 5 parts by weight of a toughening agent is introduced into the cement slurry system, the high-temperature stabilizer, high-temperature enhancer and toughening agent can synergistically control the rate and product types of the hydration reaction, further improving the high-temperature strength of the cement slurry system.

[0035] Furthermore, the cement slurry system comprises 0.5-1.5 parts by weight of a toughening agent.

[0036] According to the present invention, preferably, the toughening agent is selected from fibers with a length of 1-19 mm and a diameter of 0.1-10 μm. Using fibers of this size as toughening agents can enhance the toughness of cement paste and can also serve as hydration nucleation sites to induce hydration.

[0037] According to the present invention, preferably, the fiber is selected from at least one of carbon fiber, boron fiber and basalt fiber. Carbon fiber, boron fiber and basalt fiber have the characteristics of high strength, high modulus and high temperature resistance. Using them as toughening agents can enhance the strength and toughness of cement paste, and can also act as hydration nucleation points to induce hydration.

[0038] According to a preferred embodiment of the present invention, the cement slurry system comprises the following components in parts by weight: 100 parts of oil well cement, 20-80 parts of high temperature stabilizer, 15-80 parts of high temperature enhancer, 5 parts by weight or less of toughening agent, 0.5-6 parts of retarder, 2-10 parts of fluid loss reducer, 0.1-2 parts of defoaming agent and 35-90 parts of water.

[0039] According to a more preferred embodiment of the present invention, the cement slurry system comprises the following components in parts by weight: 100 parts of oil well cement, 40-50 parts of high temperature stabilizer, 30-40 parts of high temperature enhancer, 0.5-1.5 parts of toughening agent, 2.5-4.5 parts of retarder, 7-8 parts of fluid loss reducer, 0.4-0.6 parts of defoaming agent and 50-60 parts of water.

[0040] According to the present invention, preferably, the cement slurry system further comprises less than 2 parts by weight of a dispersant, preferably less than 1 part by weight.

[0041] According to the present invention, preferably, the dispersant is selected from polycarboxylic acid dispersants and / or ketone-aldehyde condensates.

[0042] According to the present invention, preferably, the cement slurry system has a density of 1.88-1.9 g / cm 3 When cured at 150-240℃ for 7 days after solidification, the compressive strength is above 30MPa, the flexural strength is above 6MPa, and the compressive strength is above 35MPa after 60 days.

[0043] In a preferred embodiment of the present invention, the cement slurry system has a density of 1.88-1.9 g / cm 3 When cured at 150-240℃ for 7 days after solidification, the compressive strength is above 30MPa, the flexural strength is above 8MPa, and the compressive strength is above 40MPa after 60 days.

[0044] The second aspect of the present invention provides an application of the cement slurry system provided by the present invention in high-temperature deep well cementing, preferably in deep well cementing at a curing temperature of 150-240° C. The application method is: the cement slurry is applied for cementing in a deep well, solidified into a cement ring in the annular space, and the compressive strength of the cement ring does not decline in 7-60 days.

[0045] The present invention will be described in detail below through examples. The reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the raw materials, instruments and equipment used, etc., can all be purchased from the market or can be obtained by existing methods; the reagent dosage, unless otherwise specified, is the reagent dosage in conventional experimental operations; the experimental methods, unless otherwise specified, are all conventional methods. The reagents and determination methods involved in the following examples and comparative examples are as follows:

[0046] The oil well cement was Grade G cement purchased from Jiahua Cement Plant;

[0047] AMPS multipolymer was purchased from Texas Shelf, brand SCR180L;

[0048] The fluid loss additive was a copolymer of AMPS and acrylamide, purchased from Texas Shelf, with the brand name SCF-J;

[0049] Prepared according to GB / T 19139-2012 standard, density is 1.85-1.95g / cm 3 Cement slurry system;

[0050] The density of cement slurry system is determined according to the method specified in GB / T 19139-2012;

[0051] The fluidity of cement slurry system is determined according to the method specified in GB / T 8077-2012;

[0052] The API water loss of cement slurry system is determined according to the method specified in GB / T 19139-2012;

[0053] The thickening time of cement slurry system is determined according to the method specified in GB / T 19139-2012;

[0054] The compressive strength of the cement slurry system is determined according to the method specified in GB / T 19139-2012;

[0055] The flexural strength of the cement slurry system is determined according to the method specified in GB / T 17671-2021.

[0056] The following examples are used to illustrate the preparation of cement slurry systems.

[0057] Example 1

[0058] The cement slurry system comprises the following components in parts by weight: 100 parts of oil well cement, 40 parts of high temperature stabilizer, 30 parts of high temperature enhancer, 1.5 parts of toughening agent, 2.5 parts of retarder, 7 parts of fluid loss reducer, 0.5 parts of defoamer and 59 parts of clean water to prepare the cement slurry system.

[0059] The high temperature stabilizer is prepared by mixing quartz sand with an average particle size of 109 μm, quartz sand with an average particle size of 80 μm, microsilica powder with an average particle size of 9 μm and nano silicon dioxide with an average particle size of 25 nm in a weight ratio of 7:7:5:1;

[0060] The high temperature enhancer is a mixture of epidote with an average particle size of 48 μm and boehmite with an average particle size of 13 μm in a weight ratio of 25:5;

[0061] The toughening agent is basalt fiber with a length of 5 mm and a diameter of 8 μm;

[0062] The retarder is made of tartaric acid and AMPS multipolymer SCR180L mixed in a weight ratio of 1:9;

[0063] The defoaming agent is a polysiloxane silicone defoaming agent (purchased from Texas Continental Shelf, brand name SCFD-2).

[0064] Example 2

[0065] The cement slurry system comprises the following components in parts by weight: 100 parts of oil well cement, 40 parts of high temperature stabilizer, 35 parts of high temperature enhancer, 0.5 parts of toughening agent, 4.5 parts of retarder, 8 parts of fluid loss reducer, 0.5 parts of defoamer and 52 parts of clean water to prepare the cement slurry system.

[0066] The high temperature stabilizer is prepared by mixing quartz sand with an average particle size of 109 μm, microsilica powder with an average particle size of 9 μm, and nano silicon dioxide with an average particle size of 25 nm in a weight ratio of 15:4:1;

[0067] The high temperature enhancer is prepared by mixing pyrophyllite with an average particle size of 45 μm and sillimanite with an average particle size of 25 μm in a weight ratio of 25:10;

[0068] The toughening agent is a carbon fiber with a length of 5 mm and a diameter of 6 μm;

[0069] The retarder, fluid loss reducer and defoamer are the same as those in Example 1.

[0070] Example 3

[0071] The cement slurry system comprises the following components in parts by weight: 100 parts of oil well cement, 50 parts of high temperature stabilizer, 40 parts of high temperature enhancer, 1.5 parts of toughening agent, 4 parts of retarder, 7 parts of fluid loss reducer, 0.5 parts of defoamer and 51 parts of clean water to prepare the cement slurry system.

[0072] The high temperature stabilizer is prepared by mixing quartz sand with an average particle size of 109 μm, microsilica powder with an average particle size of 9 μm, and nano silicon dioxide with an average particle size of 25 nm in a weight ratio of 21:3:1;

[0073] The high temperature enhancer is prepared by mixing pyrophyllite with an average particle size of 45 μm and actinolite with an average particle size of 75 μm in a weight ratio of 25:10;

[0074] The toughening agent is basalt fiber with a length of 5 mm and a diameter of 8 μm;

[0075] The retarder, fluid loss reducer and defoamer are the same as those in Example 1.

[0076] Example 4

[0077] The cement slurry system was prepared according to the method of Example 2, except that the quartz sand, microsilica powder and nano silicon dioxide in the high temperature stabilizer were mixed in a weight ratio of 8:4:1. The cement slurry system was prepared.

[0078] Example 5

[0079] A cement slurry system was prepared according to the method of Example 2, except that the average particle size of the quartz sand in the high temperature stabilizer was 200 μm, the average particle size of the microsilica powder was 15 μm, and the average particle size of the nano-silicon dioxide was 200 nm. A cement slurry system was prepared.

[0080] Example 6

[0081] A cement slurry system was prepared according to the method of Example 2, except that the average particle size of the quartz sand in the high temperature stabilizer was 150 μm, the average particle size of the microsilica powder was 5 μm, and the average particle size of the nano-silicon dioxide was 50 nm. A cement slurry system was prepared.

[0082] Example 7

[0083] A cement slurry system was prepared according to the method of Example 2, except that the high temperature enhancer was a mixture of pyrophyllite with an average particle size of 45 μm and sillimanite with an average particle size of 25 μm in a weight ratio of 25:20. A cement slurry system was prepared.

[0084] Example 8

[0085] A cement slurry system was prepared according to the method of Example 2, except that the high temperature enhancer was a mixture of pyrophyllite with an average particle size of 45 μm and boehmite with an average particle size of 13 μm in a weight ratio of 25:10. A cement slurry system was prepared.

[0086] Example 9

[0087] The cement slurry system was prepared according to the method of Example 2, except that polypropylene fiber (purchased from Texas Shelf, brand SFP-2) was selected as a toughening agent to obtain a cement slurry system.

[0088] Example 10

[0089] The cement slurry system was prepared according to the method of Example 2, except that the amount of toughening agent was different. Specifically, the cement slurry system contained the following components in parts by weight: 100 parts of oil well cement, 40 parts of high temperature stabilizer, 35 parts of high temperature enhancer, 2 parts of toughening agent, 4.5 parts of retarder, 8 parts of fluid loss reducer, 0.5 parts of defoamer and 52 parts of clean water to prepare the cement slurry system.

[0090] Embodiment 11

[0091] The cement slurry system was prepared according to the method of Example 2, except that the weight percentage of the high temperature stabilizer was different. Specifically, the cement slurry system contained the following components in weight percentage: 100 parts of oil well cement, 80 parts of high temperature stabilizer, 35 parts of high temperature enhancer, 0.5 parts of toughening agent, 4.5 parts of retarder, 8 parts of fluid loss reducer, 0.5 parts of defoamer and 68 parts of clean water to prepare the cement slurry system.

[0092] Comparative Example 1

[0093] The cement slurry system was prepared according to the method of Example 2, except that the cement slurry system did not contain a high temperature enhancer and a toughening agent, and the high temperature stabilizer did not contain microsilica powder and nano silicon dioxide. Specifically, the cement slurry system contained the following components in parts by weight: 100 parts of oil well cement, 40 parts of quartz sand with an average particle size of 109 μm, 4.5 parts of a retarder, 8 parts of a fluid loss reducer, 0.5 parts of a defoamer and 38 parts of clean water, and the obtained density was 1.9 g / cm 3 cement slurry system.

[0094] Comparative Example 2

[0095] The cement slurry system was prepared according to the method of Example 2, except that the cement slurry system did not contain a high temperature enhancer and a toughening agent. Specifically, the cement slurry system contained the following components in parts by weight: 100 parts of oil well cement, 40 parts of high temperature stabilizer, 4.5 parts of retarder, 8 parts of fluid loss reducer, 0.5 parts of defoamer and 38 parts of clean water, and the obtained density was 1.9 g / cm 3 cement slurry system.

[0096] Comparative Example 3

[0097] The cement slurry system was prepared according to the method of Example 2, except that the weight percentage of the high temperature enhancer in the cement slurry system was different. Specifically, the cement slurry system contained the following components in weight percentage: 100 parts of oil well cement, 40 parts of high temperature stabilizer, 5 parts of high temperature enhancer, 0.5 parts of toughening agent, 4.5 parts of retarder, 8 parts of fluid loss reducer, 0.5 parts of defoamer and 40 parts of clean water, and the obtained density was 1.9 g / cm 3 cement slurry system.

[0098] Comparative Example 4

[0099] The cement slurry system was prepared according to the method of Example 2, except that the weight percentage of the high temperature stabilizer in the cement slurry system was different. Specifically, the cement slurry system contained the following components in weight percentage: 100 parts of oil well cement, 10 parts of high temperature stabilizer, 35 parts of high temperature enhancer, 0.5 parts of toughening agent, 4.5 parts of retarder, 8 parts of fluid loss reducer, 0.5 parts of defoamer and 40 parts of clean water, and the obtained density was 1.9 g / cm 3 cement slurry system.

[0100] Comparative Example 5

[0101] A cement slurry system was prepared according to the method of Example 2, except that the high temperature stabilizer did not contain microsilica powder and nano silicon dioxide. Specifically, the cement slurry system contained the following components in parts by weight: 100 parts of oil well cement, 40 parts of quartz sand with an average particle size of 109 μm, 35 parts of high temperature enhancer, 0.5 parts of toughening agent, 4.5 parts of retarder, 8 parts of fluid loss reducer, 0.5 parts of defoamer and 52 parts of clean water to prepare the cement slurry system. The prepared cement slurry system had some sedimentation and poor suspension stability.

[0102] Comparative Example 6

[0103] The cement slurry system was prepared according to the method of Example 2, except that α-Al2O3 with an average particle size of 50 μm was selected as a high temperature enhancer. A cement slurry system was prepared.

[0104] Test Case

[0105] The density, fluidity, API water loss, thickening time, compressive strength of the cement paste formed after curing at 150-240° C. for 7-60 days, and flexural strength after 7 days of the cement slurry systems prepared in the embodiments and comparative examples were measured respectively. The results are shown in Table 1.

[0106] Table 1

[0107]

[0108] It can be seen from the above embodiments, comparative examples and Table 1 that the high temperature strength decay resistant cement slurry system of the present invention has adjustable density and thickening time, good fluidity, small water loss, high strength of cement paste formed after hardening, and a compressive strength of more than 30 MPa after curing for 7 days at 150-240°C, and does not decay at high temperature. The conventional density (1.88-1.9 g / cm 3 The compressive strength of cement paste formed by the cement slurry system is above 40MPa after curing for 30d and 60d at 220℃ and 240℃; while the compressive strength of cement paste formed by the cement slurry system prepared in Comparative Examples 1-4 after curing for 7d at 220℃ is below 21MPa, and there is a long-term strength decline phenomenon. The suspension stability of the slurry in Comparative Example 5 is poor, and sand deposition occurs. Therefore, the cement slurry system of the present invention is far superior to the conventional sand-added cement system, and fully meets the technical requirements of deep and ultra-deep high-temperature and high-pressure cementing construction.

[0109] In addition, Example 4 changes the weight ratio of quartz sand, microsilica powder and nano-silica in the high-temperature stabilizer, Examples 5 and 6 change the average particle size of quartz sand, microsilica powder and nano-silica in the high-temperature stabilizer, Example 7 changes the weight ratio of pyrophyllite and sillimanite in the high-temperature enhancer, Example 8 changes the matching method of the high-temperature enhancer, Example 9 changes the type of toughening agent, Example 10 changes the amount of toughening agent, and Example 11 changes the amount of high-temperature stabilizer. Compared with Example 2, the compressive strength of the cement slurry cured for 7 days at 150-240°C is reduced, but it does not decay at high temperature and continues to grow. This shows that the high-temperature stabilizer, high-temperature enhancer and toughening agent selected by the present invention have a good synergistic effect within a certain ratio range, and can further improve the compressive strength of the cement slurry system at high temperature after solidification.

[0110] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. An oil well cementing slurry system, characterized in that: The cement slurry system comprises the following components in parts by weight: 100 parts of oil well cement, 20-80 parts of high temperature stabilizer, 15-80 parts of high temperature enhancer, 0.5-6 parts of retarder, 2-10 parts of fluid loss reducer, 0.1-2 parts of defoamer and 35-90 parts of water; Wherein, the high temperature stabilizer is a mixture of quartz sand, microsilica powder and nano silicon dioxide having different average particle sizes; The high temperature enhancer is selected from at least one of pyrophyllite, epidote, actinolite, diaspore, sillimanite and boehmite.

2. The cement slurry system according to claim 1, characterized in that: The average particle size of the quartz sand is 75-180 μm, the average particle size of the microsilica powder is less than or equal to 10 μm, and the average particle size of the nano-silicon dioxide is 1-100 nm; Preferably, the weight ratio of the quartz sand, the microsilica powder and the nano-silicon dioxide contained in the high-temperature stabilizer is (10-25):(3-5):

1.

3. The cement slurry system according to claim 1 or 2, characterized in that: The average particle size of the high temperature enhancer is 5-80 μm; Preferably, the high temperature enhancer is a mixture of epidote and boehmite, a mixture of pyrophyllite and sillimanite, or a mixture of pyrophyllite and actinolite; Preferably, when the high temperature enhancer is a mixture of epidote and boehmite, the weight ratio of epidote to boehmite is (20-30):(3-10); when the high temperature enhancer is a mixture of pyrophyllite and sillimanite, the weight ratio of pyrophyllite to sillimanite is (20-30):(5-15); when the high temperature enhancer is a mixture of pyrophyllite and actinolite, the weight ratio of pyrophyllite to actinolite is (20-30):(5-20).

4. The cement slurry system according to any one of claims 1 to 3, characterized in that: The retarder is selected from at least one of inorganic acid, 2-acrylamide-2-methylpropanesulfonic acid copolymer, tartaric acid, citric acid and phosphate, preferably a mixture of tartaric acid and 2-acrylamide-2-methylpropanesulfonic acid copolymer; Preferably, the weight ratio of the tartaric acid to the 2-acrylamide-2-methylpropanesulfonic acid multipolymer is (1-5):(5-20).

5. The cement slurry system according to any one of claims 1 to 4, characterized in that: The fluid loss additive is a polymer; Preferably, the polymer is a copolymer comprising structural units derived from 2-acrylamido-2-methylpropanesulfonic acid and structural units derived from acrylamide; Preferably, the defoaming agent is selected from silicone defoaming agents and / or tributyl phosphate defoaming agents.

6. The cement slurry system according to any one of claims 1 to 5, characterized in that: The cement slurry system further comprises less than 5 parts by weight of a toughening agent; Preferably, the toughening agent is selected from fibers having a length of 1-19 mm and a diameter of 0.1-10 μm; Preferably, the fiber is selected from at least one of carbon fiber, boron fiber and basalt fiber.

7. The cement slurry system according to claim 6, characterized in that: The cement slurry system comprises the following components in parts by weight: 100 parts of oil well cement, 40-50 parts of high temperature stabilizer, 30-40 parts of high temperature enhancer, 0.5-1.5 parts of toughening agent, 2.5-4.5 parts of retarder, 7-8 parts of fluid loss reducer, 0.4-0.6 parts of defoamer and 50-60 parts of water.

8. The cement slurry system according to any one of claims 1 to 7, characterized in that: The cement slurry system further comprises less than 2 parts by weight of a dispersant; Preferably, the dispersant is selected from polycarboxylic acid dispersants and / or ketone-aldehyde condensates.

9. The cement slurry system according to any one of claims 1 to 8, characterized in that: The cement slurry system has a density of 1.88-1.9 g / cm 3 When solidified and cured at 150-240℃ for 7 days, the compressive strength is above 30MPa, the flexural strength is above 6MPa, and the compressive strength is above 35MPa after 60 days; Preferably, the cement slurry system has a density of 1.88-1.9 g / cm 3 When cured at 150-240℃ for 7 days after solidification, the compressive strength is above 30MPa, the flexural strength is above 8MPa, and the compressive strength is above 40MPa after 60 days.

10. Use of the cement slurry system according to any one of claims 1 to 9 in high-temperature deep well cementing, preferably in deep well cementing at a curing temperature of 150-240°C.

Citation Information

Patent Citations

  • High-strength high-toughness high-temperature-resistant oil well cement slurry system as well as preparation method and design method thereof

    CN106833567A

  • Ultrahigh-temperature high-strength tough cement paste system

    CN112341067A

  • Ultrahigh-strength tough cement paste system for well cementation as well as preparation and application thereof

    CN112939527A

  • Oil well cement with high temperature resistance and strength decline inhibition as well as preparation method and application of oil well cement

    CN113683354A

  • Large-temperature-difference well cementation cement paste and preparation method thereof

    CN114380540A

Cited By

  • Oil and gas well cementing cement high-temperature stabilizer and preparation method thereof

    CN120698720A

  • Preparation method and application of high-temperature cement stone strength decline inhibitor

    CN121698598A

  • A method for preparing a high-temperature cement stone strength degradation inhibitor and its application

    CN121698598B

  • Thermally conductive cement slurry and preparation method therefor

    WO2026208128A1